INVESTIGATING CERVICAL RADICULOPATHY IN CHENNAI, INDIA: A POPULATION-BASED RESEARCH STUDY - V, PAVITHRALOCHANI; (NEUROLOGY), MPT; MIAP, MMTFI (South Eastern European Journal of Public Health, 2024)
Aims: The aim of this study was to find out the prevalence of cervical radiculopathy among the population of Chennai with neck pain. Objectives: The target of this study was to lay out the connection between cervical radiculopathy and neck torment and to figure out the level of incapacity by utilizing The Northwick Park Neck pain Survey (NPQ). Background: Cervical radiculopathy, regularly called a "crushed nerve," happens when a nerve in the neck is irritated or pressed where it branches from the spinal rope concerning explicit neurologic and external musculoskeletal conditions in the neck and upper limbs. Materials and Methods: A general evaluation was conducted on 1000 samples in Chennai who showed neck discomfort as part of the prevalence investigation in order to identify cervical radiculopathy. The samples were included using the Spurling test and the Northwick Park Neck Pain Survey (NPQ). Where, 300 people were identified with cervical radiculopathy. Results: According to the data analysis, the study reveals that cervical radiculopathy, a condition characterised by radiating pain in the upper limbs, is diagnosed in 30% of patients with neck pain. Males experienced cervical radiculopathy at a higher rate than females. Conclusion: This study shows that cervical radiculopathy is common among different types of professionals experiencing neck pain, and that it positively correlates with gender.